Cr-si-based hexagonal flaky multi-phase nanomaterial, and preparation method and application thereof

CN122918503APending Publication Date: 2026-10-16SHANGHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611009121.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种Cr-Si基六边形片状多相纳米材料及其制备方法,以解决现有技术中复合涂层界面不稳定、结构不可控及高温性能不足的问题,并进一步提供其在高温防护涂层中的应用

Benefits of technology

1.本发明采用直流电弧等离子体原位高温合成工艺,实现了Cr-Si基六边形片状多相纳米材料的一步法制备,在单一反应过程中同步完成Cr与Si组分的蒸发、气相反应及纳米结构构筑,无需复杂的后续热处理或多步化学反应过程,显著简化了制备流程并缩短了反应周期。与传统固相烧结法、溶胶–凝胶法及化学沉积法相比,本发明具有反应效率高、工艺流程短及易于连续化生产等优点,有利于降低制备成本并实现规模化制备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918503A_ABST
    Figure CN122918503A_ABST
Patent Text Reader

Abstract

The application relates to the field of high-temperature structural materials and surface engineering technology, and discloses a Cr-Si-based hexagonal flaky multi-phase nano material and a preparation method and application thereof. The method takes high-purity Cr powder and Si powder as raw materials, obtains anode target material through pressing, adopts direct current arc plasma technology in a closed reaction system, realizes in-situ gas phase evaporation, reaction and condensation forming processes of the material in a CO2 and inert gas mixed atmosphere, forms active species of Cr and Si, reacts with an oxygen source to generate Cr2O3 and SiO2 phases, forms a hexagonal flaky or quasi-hexagonal flaky nano structure in a cooling process, the SiO2 phase is enriched in the inner core area, the Cr2O3 phase is distributed on the outer layer, and a core-shell multi-phase heterogeneous structure is constructed. The material has stable interface structure and structure controllability. The material can be used for high-temperature protective coatings and has good oxidation resistance and wear resistance in high-temperature oxidation and friction and wear environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of high-temperature structural materials and surface engineering technology, specifically relating to a Cr-Si based hexagonal sheet-like multiphase nanomaterial prepared by a DC arc plasma method, and particularly its application in high-temperature protective coatings. Technical Background In the fields of high-temperature metallurgy and energy equipment, such as blast furnace tuyeres, burner nozzles, and various hot-end structural components, materials are subjected to complex operating conditions such as high-temperature oxidation, thermal shock, and high-speed airflow erosion for extended periods. Under these service conditions, the material surface is prone to problems such as oxide layer peeling, thermal stress-induced cracking, and localized structural failure, thereby affecting the stability and service life of the equipment.

[0002] To improve the environmental adaptability of base materials, high-temperature protective coatings are typically applied to their surfaces. Currently, commonly used protective systems mainly include Cr2O3, SiO2, and their composite systems. Cr2O3 materials can form a relatively dense oxide film under high-temperature conditions, providing some barrier to oxygen diffusion. However, under conditions of high-temperature gradient changes or thermo-mechanical coupling during service, thermal stress concentration may occur at the interface, inducing microcrack initiation and propagation, thus affecting structural integrity. SiO2 materials possess excellent high-temperature chemical stability and low oxygen diffusivity, effectively enhancing the system's resistance to high-temperature oxidation. However, its intrinsic mechanical load-bearing capacity is relatively low, and localized structural failure may occur under complex service load conditions.

[0003] To address the aforementioned issues, existing technologies attempt to composite Cr-based and Si-based components to achieve complementary properties. However, these composite systems are mostly prepared through mechanical mixing or multi-step deposition processes, and their structural characteristics and interface states largely depend on subsequent process control, thus still exhibiting the following shortcomings: (1) The interface bonding between the components depends on the external process, and the interface stability is insufficient; (2) The spatial distribution of the components in the composite structure lacks controllability, making it difficult to form an effective synergistic effect; (3) The powder morphology is mostly spherical or irregular particles, and the stacking method is random during the coating construction process, making it difficult to form a stable and dense structure; (4) During high-temperature service, multiphase components are prone to migration or separation, affecting the long-term stability of the coating.

[0004] Therefore, it is necessary to provide a composite powder that can achieve multiphase synergistic distribution and has stable geometric morphology during the formation process, so as to improve the problems of insufficient interface stability and uncontrollable structure in the existing protective coating system. Summary of the Invention

[0005] The purpose of this invention is to provide a Cr-Si based hexagonal sheet-like multiphase nanomaterial and its preparation method, to solve the problems of unstable interface, uncontrollable structure, and insufficient high-temperature performance in existing composite coatings, and to further provide its application in high-temperature protective coatings. The method is carried out in a closed reaction system, using DC arc plasma as the energy source. Through the synergistic effect of Cr-Si material evaporation, oxygen-containing gas decomposition, and in-situ oxide recombination, the generation of the Cr nanophase, the formation of the SiO2 phase, and the construction of the Cr2O3 outer layer are simultaneously controlled with the hexagonal sheet-like structure.

[0006] Technical solution To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a Cr-Si based hexagonal sheet-like multiphase nanomaterial comprising hexagonal sheet-like structural particles. These particles are composed of a Cr₂O₃ phase and a SiO₂ phase, exhibiting an overall hexagonal sheet-like or quasi-hexagonal sheet-like nanoparticle morphology. The particle size is preferably 10-200 nm. The SiO₂ phase is located within the particle or exists as a core structure, while the Cr₂O₃ phase is distributed in the outer region, forming a core-shell or quasi-core-shell heterostructure. In the hexagonal sheet-like structural particles, the SiO₂ core is an amorphous or low-crystallinity structure, while the outer Cr₂O₃ is a crystalline oxide shell, forming a stable heterogeneous interface between the two. This structure is beneficial for improving the material's high-temperature stability, oxidation resistance, and interfacial bonding strength. Simultaneously, the outer Cr₂O₃ layer protects the internal SiO₂, thereby enhancing the material's structural stability in high-temperature and complex environments.

[0007] The “Cr-Si based hexagonal sheet multiphase nanomaterial” referred to in this invention refers to a nanomaterial obtained from raw materials containing Si and Cr, which contains a hexagonal sheet structure formed by the joint participation of Cr2O3 phase and SiO2 phase; wherein “Cr-Si based” means that the formation of the hexagonal sheet structure in the material depends on the simultaneous presence of Si and Cr in the raw materials, rather than referring to a binary compound with a specific stoichiometric ratio.

[0008] This invention also provides a method for preparing Cr-Si based hexagonal sheet-like multiphase nanomaterials, comprising the following steps: (1) Mix elemental Cr powder and elemental Si powder and press them into a dense anode target, and place it in a DC arc plasma reaction device, and set a conductive material as the cathode to form an arc discharge system; (2) A mixture of CO2 and inert gas is introduced into the reaction chamber; (3) Running a DC arc; (4) After the reaction is completed, the product is cooled and collected to obtain Cr-Si based hexagonal sheet multiphase nanomaterials.

[0009] Under the action of high-temperature plasma from a DC arc, CO2 is activated and provides an oxygen source to form active oxygen species. The anode material undergoes evaporation and gas-phase transport processes. The Cr and Si components simultaneously undergo gas-phase activation reactions and participate in the oxidation process together with CO2, forming active gas-phase species containing Cr-O and Si-O. These gas-phase species then undergo synergistic nucleation, condensation, and collisional growth processes under a temperature gradient, forming Cr-Si-O multiphase primary nanoparticles. During subsequent cooling, the Cr oxide phase crystallizes and induces the particles to form hexagonal or quasi-hexagonal plate-like morphologies. Simultaneously, the SiO2 phase selectively enriches and deposits on the particle surface and / or at the interface, thereby constructing a core-shell or nested multiphase composite structure. The hexagonal or quasi-hexagonal plate-like structure is driven by the Cr2O3 crystal growth process and accompanied by SiO2 phase interface enrichment regulation.

[0010] As a preferred technical solution of the present invention, after the DC arc operation ends, the reaction products are collected after cooling in a closed system to obtain Cr-Si based hexagonal sheet-like multiphase nanomaterials.

[0011] As a preferred technical solution of the present invention, in step (1), elemental Cr powder and elemental Si powder are used as raw materials, wherein Cr is preferably high-purity Cr powder and Si is preferably high-purity Si powder, and their purity is not less than 99.9%; after mixing Cr powder and Si powder according to a set mass ratio, mechanical grinding is performed to homogenize them, and they are pressed into a dense anode target; at the same time, graphite electrode or highly conductive material is selected as cathode to ensure the stability of DC arc discharge process.

[0012] This invention discovers that as long as Si and chromium (Cr) are present simultaneously in the raw materials, regardless of their mixing ratio, the resulting product will contain hexagonal plate-like structures. The ratio of Si to Cr in the raw materials does not determine the presence or absence of hexagonal plate-like structures, but rather affects their content. Specifically, when the Si content in the raw materials is too low, the content of hexagonal plate-like structures is low, and the product mainly forms as independent nanoparticles of Cr₂O₃ and SiO₂ or a SiO₂-enriched phase. Preferably, the mass ratio of Si to Cr in the raw materials is 2:1 to 3:1. Within this preferred ratio range, the synthesis success rate of hexagonal plate-like structures is high, and the content of hexagonal plate-like structure particles in the product is high, which is beneficial for obtaining excellent wear resistance and oxidation resistance.

[0013] As a preferred technical solution of the present invention, the reaction process in step (2) is carried out in a closed reaction system. The mixed gas consists of CO2 and He. The total pressure of the reaction system is controlled within the range of 0.1 MPa to 0.5 MPa (0.2 MPa to 0.3 MPa). The volume fraction of CO2 is 5% to 50% (preferably 30% to 40%). He participates in the discharge process as an inert and stable gas to maintain the stability of plasma discharge.

[0014] As a preferred technical solution of the present invention, in step (3), under the action of DC arc, the arc current is controlled within the range of 50 A to 300 A (preferably 150 A to 180 A) so that the anode material evaporates and enters the gas phase environment. At the same time, the Cr and Si components react with CO2 in the gas phase to generate gas phase species containing Cr-O and Si-O, and under the action of temperature gradient, they condense and collide to grow, forming Cr-Si-O multiphase nanoparticles with a particle size preferably of 10 nm to 200 nm.

[0015] As a preferred technical solution of the present invention, the distribution ratio of SiO2 phase in particles and the continuity of Cr2O3 outer layer coating are controlled by adjusting the partial pressure of CO2 and plasma energy (power of DC arc).

[0016] As a preferred technical solution of the present invention, in step (2), the power of the DC arc is 2.8 kW to 3.2 kW.

[0017] As a preferred technical solution of the present invention, in step (2), the running time of the DC arc is 5 min to 6 min.

[0018] This invention achieves synergistic control over the evaporation behavior, oxidation reaction process, and gas-phase condensation process of Cr and Si by adjusting key process parameters such as DC arc current, reaction pressure, CO2 partial pressure, and He ratio. This allows for effective control over the particle size, phase composition, and microstructure of the products. He not only acts as an inert gas to maintain discharge stability but also, due to its high thermal conductivity and ionization characteristics, effectively increases the temperature and energy density of the plasma region, enhances the evaporation efficiency of the anode material, and improves the gas-phase reaction activity, thereby promoting the formation of hexagonal nanoparticles and the development of crystal structures. Through the adjustment of the above parameters, structurally stable and uniformly dispersed Cr-Si based hexagonal sheet-like multiphase nanomaterials are obtained.

[0019] As a preferred technical solution of the present invention, the product is collected by water cooling control after the reaction is completed in step (4).

[0020] The Cr-Si based hexagonal sheet-like multiphase nanomaterials of this invention exhibit good oxidation resistance and wear resistance under high-temperature oxidation and friction wear environments.

[0021] The present invention also provides the application of the Cr-Si based hexagonal sheet multiphase nanomaterial in the preparation of high-temperature protective coatings, oxidation-resistant functional materials or surface-reinforcing phases.

[0022] The high-temperature protective coating is applied to the surface of blast furnace tuyeres, burner nozzles, or high-temperature hot-end structural components to improve the components' resistance to high-temperature oxidation and heat. Service life under force coupling environment. The oxidation-resistant functional material is used to prepare high-temperature oxidation-resistant components, and the surface-reinforcing phase is used to improve the surface hardness and wear resistance of the matrix material.

[0023] Beneficial effects Compared with the prior art, the present invention has the following beneficial effects: 1. This invention employs a DC arc plasma in-situ high-temperature synthesis process to achieve a one-step preparation of Cr-Si based hexagonal sheet-like multiphase nanomaterials. The evaporation of Cr and Si components, gas-phase reaction, and nanostructure construction are simultaneously completed in a single reaction process, eliminating the need for complex subsequent heat treatments or multi-step chemical reactions. This significantly simplifies the preparation process and shortens the reaction cycle. Compared with traditional solid-state sintering, sol-gel, and chemical deposition methods, this invention offers advantages such as high reaction efficiency, short process flow, and ease of continuous production, which helps reduce preparation costs and achieve large-scale preparation. 2. The core-shell or quasi-core-shell multiphase nanostructure with SiO2 as the core and Cr2O3 as the outer coating obtained by the present invention effectively solves the problems of uneven particle size distribution, unstable interface structure and poor repeatability in existing methods. 3. This invention uses high-purity Cr powder and Si powder as the main raw materials, CO2 as the oxidizing medium in the reaction atmosphere, and He as a supplement to maintain plasma discharge stability and increase the temperature of the discharge region. The raw materials are widely available and relatively inexpensive. Furthermore, the entire reaction process does not require the introduction of complex organic precursors or toxic chemical reagents, exhibiting good environmental friendliness. The DC arc plasma process features high temperature, high energy density, and fast reaction rate, enabling the rapid generation of high-purity nanomaterials, reducing impurity introduction, improving material purity and consistency, and is suitable for continuous industrial production. 4. The hexagonal plate-like particles prepared by this invention have unique heterogeneous interface structure characteristics. The internal SiO2 phase has good thermal and chemical stability, while the outer Cr2O3 shell provides excellent oxidation resistance and surface protection. At the same time, the presence of the multiphase heterogeneous interface helps to alleviate thermal stress concentration and enhance the interfacial bonding stability, thereby improving the structural stability and durability of the material under high temperature, oxidation and complex service environments. It has good application prospects in the fields of high temperature protective coatings, oxidation-resistant functional materials and surface-reinforcing phases. Attached Figure Description

[0024] Figure 1 This is a flowchart of a method for preparing Cr-Si-based multiphase composite nanomaterials according to the present invention; Figure 2 Transmission electron microscope image of the Cr-Si based multiphase composite nanomaterial prepared in Example 1; Figure 3 The elemental distribution map of the Cr-Si based multiphase composite nanomaterial prepared in Example 1 is shown in the transmission electron microscopy-energy dispersive spectroscopy (TEM-EDS) diagram. Figure 4 Transmission electron microscope image of the Cr-Si based multiphase composite nanomaterial prepared in Example 2; Figure 5 Transmission electron microscope image of the Cr-Si based multiphase composite nanomaterial prepared in Example 3; Figure 6 Transmission electron microscope image of the crystalline Cr2O3 nanomaterial prepared for Comparative Example 1. Detailed Implementation

[0025] The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0026] like Figure 1 As shown, this invention provides a method for preparing Cr-Si-based multiphase composite nanomaterials, comprising the following steps: High-purity Cr powder and high-purity Si powder were selected as raw materials; High-purity Cr powder and high-purity Si powder are mixed and ground to obtain chromium-silicon mixed powder; The mixed chromium-silicon powder is pressed into a tablet to obtain a Cr-Si mixture target material. The Cr-Si mixture target was placed in a DC arc device, and a mixed atmosphere of CO2 and inert gas was introduced into the closed reaction system. The target was then subjected to arc plasma evaporation to obtain Cr-Si based multiphase composite nanomaterials.

[0027] Given that high-temperature protective coatings often endure both oxidative environments and mechanical friction during actual service, to comprehensively evaluate their high-temperature suitability, the following examples included a high-temperature oxidation experiment at 800°C and a high-temperature friction and wear test to examine the coating's performance under thermal conditions. Wear resistance and structural integrity under force coupling conditions.

[0028] Example 1 A method for in-situ preparation of Cr-Si based multiphase composite nanomaterials using DC arc plasma includes the following steps: (1) Select high-purity Cr powder and Si powder with a purity of 99.9%, mix them at a mass ratio of 2:1, grind them evenly by mechanical grinding, and then press them into a dense anode target; (2) Load the prepared Cr-Si mixture target into a DC arc plasma device, and use a high-purity tungsten electrode as the cathode; (3) Evacuate the reaction chamber to 5×10 -3 After Pa, a CO2 / He mixed gas was introduced. The partial pressure of each component was adjusted so that the partial pressure of CO2 accounted for 50% of the total pressure. He was used as an inert and stable gas, and the total pressure of the system was controlled at 0.5 MPa. The DC arc current was set to 300 A and the plasma power to 2.8 kW. The in-situ reaction was carried out under the action of high-temperature plasma for 5 min. After the reaction, the plasma was cooled to room temperature by water cooling and the product was collected to obtain Cr-Si based multiphase composite nanomaterials.

[0029] Testing revealed that the Cr-Si-based multiphase composite nanomaterial prepared in this embodiment contains a large number of hexagonal plate-like particles with a particle size of 10-200 nm. The overall structure is hexagonal or quasi-hexagonal plate-like, forming a multiphase structure with SiO2 as the core, while the Cr2O3 phase is mainly distributed in the outer region. This material was used for high-temperature tribological testing, employing a pin-on-disc tribological test to evaluate its performance. The mating material was an Al2O3 ceramic disk (alumina friction pair). The test conditions were as follows: normal load 50 N, rotational speed 100 r / min, friction radius 10 mm, test temperature 800 ℃, and test time 60 min.

[0030] Its wear rate is 2.1 × 10⁻⁶. -5 mm 3 Its friction coefficient is 0.22, and its mass gain rate under high-temperature oxidation conditions of 800 °C is 0.42 mg·cm³. -2 ·h -1 .

[0031] The morphology of the Cr-Si based multiphase composite nanomaterials prepared in this embodiment under a transmission electron microscope is as follows: Figure 2 As shown, the compositional distribution of the Cr-Si-based multiphase composite nanomaterials prepared in this embodiment after DC arc plasma treatment is illustrated by transmission electron microscopy. Figure 3 As shown. Example 2 A method for in-situ preparation of Cr-Si based multiphase composite nanomaterials using DC arc plasma includes the following steps: (1) Select high-purity Cr powder with a purity of 99.9% and Si powder, mix them at a mass ratio of 3:1, grind them evenly by mechanical grinding, and then press them into a dense anode target material; (2) The prepared Cr-Si mixture target material is loaded into a DC arc plasma device, and a high-purity tungsten electrode is used as the cathode; (3) Evacuate the reaction chamber to 5×10⁻⁶ ℃. -3 After Pa, a CO2 / He mixed gas was introduced. The partial pressure of each component was adjusted so that the partial pressure of CO2 accounted for 40% of the total pressure. He was used as an inert and stable gas, and the total pressure of the system was controlled at 0.3 MPa. The DC arc current was set to 200 A and the plasma power to 3.2 kW. The in-situ reaction was carried out under the action of high-temperature plasma for 6 min. After the reaction, the plasma was cooled to room temperature by water cooling and the product was collected to obtain Cr-Si based multiphase composite nanomaterials.

[0032] Testing revealed that the Cr-Si-based multiphase nanomaterials prepared in this embodiment contained a large number of hexagonal plate-like particles with a particle size of 15–180 nm. While maintaining an overall hexagonal or quasi-hexagonal plate-like structure, the distribution ratio of the Cr2O3 phase was relatively increased, and the Cr2O3 outer layer coating was more continuous and dense. Tribological wear testing employed the pin-disc method, with an Al2O3 ceramic disk as the mating material, and the testing conditions were the same as in Example 1. The results showed a wear rate of 1.8 × 10⁻⁶. -5 mm 3 Its friction coefficient is 0.20, and its mass gain rate under high-temperature oxidation conditions at 800℃ is 0.38 mg·cm³. -2 ·h -1 .

[0033] The morphology of the Cr-Si based multiphase composite nanomaterials prepared in this embodiment is as follows: Figure 4 As shown. Example 3 A method for in-situ preparation of Cr-Si based multiphase composite nanomaterials using DC arc plasma includes the following steps: (1) Select high-purity Cr powder with a purity of 99.9% and Si powder, mix them at a mass ratio of 1:1, grind them evenly by mechanical grinding, and then press them into a dense anode target material; (2) The prepared Cr-Si mixture target material is loaded into a DC arc plasma device, and a high-purity tungsten electrode is used as the cathode; (3) Evacuate the reaction chamber to 5×10⁻⁶ ℃. -3 After Pa, a CO2 / He mixed gas was introduced. The partial pressure of each component was adjusted so that the partial pressure of CO2 accounted for 20% of the total pressure. He was used as an inert and stable gas, and the total pressure of the system was controlled at 0.15 MPa. The DC arc current was set to 50 A and the plasma power to 2.2 kW. The in-situ reaction was carried out for 4 min under the action of high-temperature plasma. After the reaction, the mixture was cooled to room temperature by water cooling and the product was collected to obtain Cr-Si based multiphase composite nanomaterials.

[0034] Testing revealed that the Cr-Si-based multiphase nanomaterials prepared in this embodiment had particle sizes ranging from 10 to 150 nm, exhibiting poor particle dispersion. However, the proportion of SiO2 phase in the system was significantly increased, while the content of Cr2O3 phase was relatively decreased. The product showed low levels of hexagonal lamellar structures, primarily existing as independent Cr2O3 and SiO2 nanoparticles or SiO2-enriched phases. Under these structural conditions, the overall interfacial heterogeneity of the material decreased, and the structural continuity was somewhat weakened. Tribological wear testing employed the pin-disc method, with an Al2O3 ceramic disk as the mating material, and the testing conditions were the same as in Example 1. The wear rate was 1.6 × 10⁻⁶. -4 mm 3 Its friction coefficient is 0.35, and its mass gain rate under high-temperature oxidation conditions at 800℃ is 0.50 mg·cm³. -2 ·h -1 .

[0035] The morphology of the Cr-Si based multiphase composite nanomaterials prepared in this embodiment is as follows: Figure 5 As shown.

[0036] Comparative Example 1 This comparative example is used to verify the effect of Si composition on the structure and morphology regulation of the product. The specific preparation method is as follows: (1) High-purity Cr powder with a purity of 99.9% was selected as the only raw material, and after being mechanically ground and mixed evenly, it was pressed into a dense anode target. (2) The prepared Cr target material is loaded into a DC arc plasma device, and a high-purity tungsten electrode is used as the cathode; (3) Evacuate the reaction chamber to 5×10⁻⁶ ℃. -3 After Pa, a CO2 / He mixed gas was introduced. The partial pressure of each component was adjusted so that the partial pressure of CO2 accounted for 30% of the total pressure. He was used as an inert and stable gas, and the total pressure of the system was controlled at 0.2 MPa. The DC arc current was set to 150 A and the plasma power to 2.8 kW. The in-situ reaction was carried out for 5 min under the action of high-temperature plasma. After the reaction was completed, the mixture was cooled to room temperature by water cooling, and the product was collected to obtain the comparative sample.

[0037] Upon testing, the product prepared in this comparative example was mainly composed of Cr oxide phase (mainly Cr2O3), with a particle size of approximately 20~300 nm. The overall morphology changed from a regular plate-like structure to a uniform cubic or near-cubic structure. The crystal shape was clear and the edges were distinct. No Si-related multiphase core-shell or composite structure characteristics were observed.

[0038] The pin-disc friction and wear test conditions were the same as in Example 1. The results showed that the wear rate of the comparative material in the high-temperature friction and wear test was 3.8 × 10⁻⁶. -4 mm 3Its friction coefficient is 0.55, and its mass gain rate under high-temperature oxidation conditions of 800 °C is 0.6 mg·cm³. -2 ·h -1 Overall, it exhibits a simple structure and wear resistance.

[0039] The morphology of crystalline Cr2O3 nanocubes after DC arc plasma treatment in Comparative Example 1 is as follows: Figure 6 As shown.

Claims

1. A method for preparing Cr-Si based hexagonal sheet-like multiphase nanomaterials, characterized in that, include: (1) Mix elemental Cr powder and elemental Si powder and press them into a dense anode target, and place it in a DC arc plasma reaction device, and set a conductive material as the cathode to form an arc discharge system; (2) A mixture of CO2 and inert gas is introduced into the reaction chamber; (3) Running a DC arc; (4) After the reaction is completed, the product is cooled and collected to obtain Cr-Si based hexagonal sheet multiphase nanomaterials.

2. The preparation method according to claim 1, characterized in that, In step (1), the purity of both Cr powder and Si powder is not less than 99.9%, and the mass ratio of elemental Cr powder to elemental Si powder is 2:1 to 3:

1.

3. The preparation method according to claim 1, characterized in that, In step (2), the total pressure of the reaction system is 0.1 MPa to 0.5 MPa, the volume fraction of CO2 is 5% to 50%, and the inert gas is He.

4. The preparation method according to claim 1, characterized in that, In step (3), the DC arc current is 50 A to 300 A.

5. The preparation method according to claim 1, characterized in that, The particle size of the nanoparticles is controlled to be 10 nm to 200 nm by adjusting the arc current.

6. The preparation method according to claim 1, characterized in that, The distribution ratio of SiO2 phase in particles and the continuity of Cr2O3 outer layer coating are controlled by adjusting the partial pressure of CO2 and plasma energy.

7. The preparation method according to claim 1, characterized in that, The power of the DC arc mentioned in step (3) is 2.8kW~3.2kW.

8. A Cr-Si based hexagonal sheet-like multiphase nanomaterial, characterized in that, The material comprises hexagonal sheet-like structured particles; the hexagonal sheet-like structured particles are composed of Cr2O3 phase and SiO2 phase, and the whole is in the form of hexagonal sheet-like or quasi-hexagonal sheet-like nanoparticle morphology, wherein the SiO2 phase is located inside the particles or exists as a core structure, and the Cr2O3 phase is distributed in the outer layer region, forming a core-shell or quasi-core-shell heterostructure.

9. The material according to claim 8, characterized in that, The SiO2 has an amorphous or low-crystallinity structure, while the Cr2O3 has a crystalline oxide structure.

10. The application of the Cr-Si based hexagonal sheet-like multiphase nanomaterial of claim 8 or 9 in the preparation of high-temperature protective coatings, oxidation-resistant functional materials or surface-reinforcing phases.

11. The application according to claim 10, characterized in that: The high-temperature protective coating is applied to the surface of blast furnace tuyeres, burner nozzles, or high-temperature hot-end structural components.